2011
DOI: 10.1161/strokeaha.111.621649
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Poor Outcomes Within 6 Months After Acute Ischemic Stroke

Abstract: Background and Purpose-Diabetes mellitus (DM) is an independent risk factor for ischemic stroke. However, controversy exists with regard to the impact of DM on prognosis after ischemic stroke in the Chinese population. We investigated the associations between DM and death, dependency, and stroke recurrence in patients after ischemic stroke onset in a nationwide, prospective registry, the China National Stroke Registry. Methods-The China National Stroke Registry consecutively recruited patients hospitalized for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
92
4
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 34 publications
15
92
4
4
Order By: Relevance
“…The increased risk of adverse poststroke outcomes with high or low eGFR might be partly explained by factors associated with decline of renal function, like anemia, oxidative stress, and inflammation, which could accelerate atherosclerosis and endothelial dysfunction (22). Our previous work has also indicated diabetes to be an independent predictor for adverse outcomes of acute stroke (23). The combination of diabetes and CKD might increase the risk of adverse stroke outcomes further.…”
Section: Discussionmentioning
confidence: 97%
“…The increased risk of adverse poststroke outcomes with high or low eGFR might be partly explained by factors associated with decline of renal function, like anemia, oxidative stress, and inflammation, which could accelerate atherosclerosis and endothelial dysfunction (22). Our previous work has also indicated diabetes to be an independent predictor for adverse outcomes of acute stroke (23). The combination of diabetes and CKD might increase the risk of adverse stroke outcomes further.…”
Section: Discussionmentioning
confidence: 97%
“…DM is an important risk factor for ischemic stroke; the reported hazard ratio (HR) for ischemic stroke was 2.3 (95% confidence interval [CI] 2.0-2.7) in individuals with DM versus those without DM. 1 Furthermore, ischemic stroke patients with DM have a poor prognosis, [2][3][4] and DM has been widely used to predict outcome after acute ischemic stroke or transient ischemic attack as an important risk factor. [5][6][7] The traditional glucose-based criteria of DM are based on a fasting plasma glucose (FPG) and oral glucose tolerance test (OGTT) (FPG ≥7.0 mmol/L and/or 2-hour OGTT ≥11.1 mmol/L).…”
mentioning
confidence: 99%
“…1 We acknowledged that the patients diagnosed with diabetes mellitus (DM) in our study could have included a few patients with stress hyperglycemia according to the definition of DM adopted in this study ("a self-reported physician diagnosis of DM, use of hypoglycemic medications [for example, insulin or sulfonylureas] during hospitalization, or hypoglycemic medication use at discharge"). However, as Dr Zhang had mentioned in his letter, it was difficult to obtain the results of oral glucose tolerance tests from all the participating patients in such a multicenter, large-sample research as ours.…”
Section: Responsementioning
confidence: 99%